LVOV EX-LIBRIS SCHOOL AS THE TRADITIONS KEEPER OF THE INTAGLIO PRINTING TECHNIQUES IN THE UKRAINIAN GRAPHIC ARTS AT THE TURN OF THE XXTH AND XXITH CENTURIES - Romanenkova, Julia; Bratus, Ivan Bratus; Myikhalchuk, Vadym; Gunka, Anna (Revista Inclusiones, 2021)
The article is devoted to the ex-libris in the context of the role of the Lvоv printmaking school in contemporary Ukrainian art. A general characteristic of Ukraine’s ex-libris is presented, the main evolution stages of the contemporary book plate are outlined, the special role of the Lvov school is emphasized, a brief comparative analysis of the stylistics of different ex-libris schools (Kiev, Odessa, Kharkov, Lvov) is carried out. The change in ex-libris role in the general character of the art process of last years (since the 1990s) is actualized and the reason for this phenomenon is argued. The preference of the Lvov school graphic arts experts for intaglio printing techniques is emphasized, the ex-libris is considered as an element of the contemporary artistic process, a communication tool in the cultural space of nowadays.